Dzielimy się doświadczeniem Effects of protamine sulfate in off-pump - Goździewicz, Marek; Němec, Petr; Zezula, Radek; Hajek, Roman; Šimek, Martin; Šantavy, Petr; Elfmark, Milan (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Aims: Hypercoagulation has been shown to exist postoperatively in off-pump coronary surgery patients. The aim of this study was to determine whether protamine sulfate administration adversely affects the postoperative coagulation status in these patients. Material and Methods: Forty consecutive patients who underwent off-pump coronary bypass surgery between December 2005 and February 2007 were randomized into two groups depending on whether (group A) or not (group B) they received protamine sulfate. Coagulation status was measured on the first and third postoperative days using thromboelastography (TEG). Postoperative blood loss was also compared between the groups. Results: On the third postoperative day all patients in both groups showed an increase in the TEG maximal amplitude (MA), confirming the presence of hypercoagulation. The MA was greater in group A than in group B (76.6 vs. 73.3 mm, respectively), but did not reach statistical significance (ANOVA p=0.40). The total blood loss did not differ significantly between groups A and B (828 vs. 878 ml, respectively). Conclusions: The results of this study suggest that the routine use of protamine sulfate in off-pump coronary surgery may not be necessary.